What Can We Learn from The Pandemic? Outline of Health System Management During the Pandemic Crisis Based on the Examples of Poland and Sweden - Sylwia NIESZPORSKA (Communications of International Proceedings, 2024)
Research motivation The concept of health system management is an extremely complex process, covering many areas of life. All activities in these areas became particularly important during the crisis that the world faced at the beginning of 2020, with the announcement of the SARS-CoV-2 Pandemic. As a result of the extremely rapid increase in illnesses and deaths caused by the virus, the governments of all countries have had to take many steps to change not only the structure of health systems by reorganising the scope of services provided but also the everyday life of citizens in the face of a completely new reality. Methodology Activities in the field of management of the Polish and Swedish health systems were reviewed, with particular reference to data from 2020 onwards. What was analysed was not only data about health state and health ratios of Polish and Swedish citizens during and directly after the pandemic but also some systemic and organizational methods of the health systems management. Main findings Objective and subjective indicators of health status, which are better and more beneficial for Swedish citizens than for Polish citizens, may undoubtedly be associated with a better organisation of Swedish health care not only during the Pandemic, but also before it. This state of affairs can also be linked to higher financial resources allocated to the sector. According to Eurostat data, in 2020 spending on health in Sweden was 11.4% of the country's GDP, while in Poland it amounted to 6.4% of its GDP.
Keywords: pandemic; SARS CoV-2; COVID-19; health systems management.